Elucidating heavy/light chain pairing preferences to facilitate the assembly of bispecific IgG in single cells. Issue 7 (3rd October 2019) - Joshi, Kamal Kishore; Phung, Wilson; Han, Guanghui; Yin, Yiyuan; Kim, Ingrid; Sandoval, Wendy; Carter, Paul J.
ABSTRACT: Multiple strategies have been developed to facilitate the efficient production of bispecific IgG (BsIgG) in single host cells. For example, we previously demonstrated near quantitative (≥90%) formation of BsIgG of different species and isotypes by combining 'knob-into-hole' mutations for heavy chain heterodimerization with engineered antigen-binding fragments (Fabs) for preferential cognate heavy/light chain pairing. Surprisingly, in this study we found high yield (>65%) of BsIgG1 without Fab engineering to be a common occurrence, i.e., observed for 33 of the 99 different antibody pairs evaluated. Installing charge mutations at both CH 1/CL interfaces was sufficient for near quantitative yield (>90%) of BsIgG1 for most (9 of 11) antibody pairs tested with this inherent cognate chain pairing preference. Mechanistically, we demonstrate that a strong cognate pairing preference in one Fab arm can be sufficient for high BsIgG1 yield. These observed chain pairing preferences are apparently driven by variable domain sequences and can result from a few specific residues in the complementarity-determining region (CDR) L3 and H3. Transfer of these CDR residues into other antibodies increased BsIgG1 yield in most cases. Mutational analysis revealed that the disulfide bond between heavy and light chains did not affect the yield of BsIgG1 . This study provides some mechanistic understanding of factors contributing to antibody heavy/light chain pairing preference and subsequently contributes to the efficient production of BsIgG in single host cells.